Studi Perbandingan Ukuran Alat Tangkap dengan Kekuatan Mesin Kapal Pukat Udang - Thohir Adhari; Sepri Sumbung; Sudirman Sudirman (Jurnal Airaha, 2015)
Size of the shrimp trawl will be proportional to the size of the propulsion power engine, that is more great tools to catch going to need a big powered ships for more economical. The goal of research is to productivity shrimp trawl and correlation of respondence between size of the fishing gear with power engine of the vessel. Methods of practice that is descriptive (describing systematically fact observation/ research about the operation the shrimp trawl and about shrimp trawl fishing gear) and quantitatively (using calculations of productivity and calculate the suitability of gear with power engine). Productivity KM. Soerya 86 is 66,4 tonnes while the corresponding data in the field catches 20,9% higher. Based on the calculations for KM. Soerya 86, size of the shrimp trawl appropriate supposed to 41,10 m while the field observations used mesh size of 18 m. Weight otter board according supposed 271,25 kg but field observation using only weight 220 kg. Otter board spacious appropriate but should 3,06 m2 observations in the field widely otter board using 2,31 m2.